The Role of the Brimob Unit of the North Sumatra Regional Police in Suppressing Anarchic Actions During Public Expression of Opinion Under Law Number 9 of 1998 - Pasaribu, Afrildhon; Rafianti, Fitri; Zarzani, T. Riza (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the role of the Mobile Brigade Unit (Brimob) of the North Sumatra Regional Police in law enforcement against individuals who engage in anarchic acts during public expression of opinion, as examined under the provisions of Law Number 9 of 1998. Freedom of expression constitutes a constitutional right of every citizen guaranteed by the 1945 Constitution of the Republic of Indonesia; however, its exercise must remain attentive to public order, security, and the rights of others. In practice, demonstrations frequently escalate into anarchic acts that potentially disrupt security stability and cause material and immaterial harm to the public and the state. The research method employed is normative legal research supported by empirical data, utilizing statutory, conceptual, and empirical approaches. Data sources were obtained through library research on legislation, legal literature, and field data relating to the execution of duties by the Mobile Brigade Corps of the Indonesian National Police within the jurisdiction of the North Sumatra Regional Police. The findings indicate that the Brimob Unit of the North Sumatra Regional Police holds a strategic role as a special operational element of the police force, particularly in the suppression of mass riots, crowd control, and the restoration of public security and order. In carrying out its duties, Brimob adheres to the principles of legality, necessity, proportionality, accountability, and respect for human rights. Enforcement actions against anarchic crowds are carried out in stages through preventive, persuasive, and repressive measures in accordance with applicable standard operating procedures. Obstacles encountered include limited personnel, inadequate infrastructure, mass provocation, dissemination of hoax information, and low levels of legal awareness among the public. It is recommended that personnel professionalism be enhanced, equipment modernized, inter-agency coordination strengthened, and legal education provided to the public so that the expression of opinion may proceed in an orderly and peaceful manner.